2016
DOI: 10.21037/jtd.2016.06.65
|View full text |Cite
|
Sign up to set email alerts
|

Giant bronchogenic cyst with pericardial defect: a case report & literature review in Japan

Abstract: Congenital pericardial defects are a rare anomaly, found during autopsy and cardiothoracic surgery. We describe a case of a 69-year-old female, with a right-sided congenital pericardial defect associated with a giant bronchogenic cyst (BC) found during surgery. The cyst was resected and the patient developed arrhythmia following surgery. A review of the literature in Japan was performed, focusing on congenital anomalies associated with pericardial defects and its pathogenesis. We paid particular attention to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Imperatori et al [ 19 ] has reported 18 cases of bronchogenic cyst with congenital pericardial defect. A number of articles[ 13 , 22 ] suggest that congenital pericardial defects may be related to bronchial cysts. At the fifth week of embryonic development, the bronchial bud develops at the tail end of the larynx and grows into the pericardioperitoneal canal, which is the future pleural cavity; during this period, the primitive heart and lungs share a common chamber and are closely linked to each other[ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Imperatori et al [ 19 ] has reported 18 cases of bronchogenic cyst with congenital pericardial defect. A number of articles[ 13 , 22 ] suggest that congenital pericardial defects may be related to bronchial cysts. At the fifth week of embryonic development, the bronchial bud develops at the tail end of the larynx and grows into the pericardioperitoneal canal, which is the future pleural cavity; during this period, the primitive heart and lungs share a common chamber and are closely linked to each other[ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…BC is also associated with various congenital anomalies of heart, chest wall and diaphragm. Imperatori A et al [9] and Kamata T et al [10] observed bronchogenic cyst with pericardial defect in adult. There is a small risk of malignant transformation within the cyst; bronchoalveolar cell carcinoma and neuroblastoma are reported with bronchogenic cyst [2].…”
Section: Vol 3 Issue 1 Jan -Mar 2017mentioning
confidence: 99%
“…[ 1 ] Smaller defects with the potential to cause strangulation should be carefully evaluated for pericardial reconstruction. [ 2 ]…”
mentioning
confidence: 99%